2006
DOI: 10.1200/jco.2005.05.0096
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss After Radiotherapy and Chemoradiotherapy: A Single, Blinded, Randomized Study

Abstract: Patients with NPC who received radiotherapy and concurrent/adjuvant chemotherapy using CDDP experienced greater sensorineural hearing loss compared with patients treated with radiotherapy alone, especially to high-frequency sounds in the speech range. Normal inner ear tissue tolerance, which was once defined only for radiotherapy patients alone, should be redefined in chemoradiotherapy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 18 publications
7
112
1
Order By: Relevance
“…Miettinen et al (1997) also found that radiotherapy enhanced the ototoxicity of CDDP in the higher speech frequencies. The results of these studies were consistent with those from case reports, which supported the idea that RT should be considered cautiously in children treated with CDDP for intracranial malignancies (Sweetow & Will, 1993;Walker et al, 1989) We conducted a single blinded randomized trial to investigate the true differences in extent, onset and clinical course of SNHL between newly diagnosed nasopharyngeal carcinoma (NPC) patients treated by RT alone and by combined chemo-RT (Low et al 2006c). Bone conduction thresholds were performed before treatment and at 1 week, 6 months, 1 year and 2 years after completion of RT.…”
Section: Chemo-radiation and Their Combined Ototoxic Effectssupporting
confidence: 76%
“…Miettinen et al (1997) also found that radiotherapy enhanced the ototoxicity of CDDP in the higher speech frequencies. The results of these studies were consistent with those from case reports, which supported the idea that RT should be considered cautiously in children treated with CDDP for intracranial malignancies (Sweetow & Will, 1993;Walker et al, 1989) We conducted a single blinded randomized trial to investigate the true differences in extent, onset and clinical course of SNHL between newly diagnosed nasopharyngeal carcinoma (NPC) patients treated by RT alone and by combined chemo-RT (Low et al 2006c). Bone conduction thresholds were performed before treatment and at 1 week, 6 months, 1 year and 2 years after completion of RT.…”
Section: Chemo-radiation and Their Combined Ototoxic Effectssupporting
confidence: 76%
“…Although cranial irradiation was not investigated in this cohort, it has been identified as a risk factor for the development of ototoxicity. [18,19] We hypothesise that the high incidence of hearing loss in these groups may be attributed to the use of cranial irradiation during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous noise exposure and renal dysfunction [18,19] were not investigated in this study owing to lack of clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Cranial RT is less ototoxic than platinum-based chemotherapy (i.e., cisplatin), but is still associated with high risk for SNHL, [1][2][3] and even more so when combined with cisplatin. 4,5 Risk and severity of SNHL increases when a higher radiation dose is delivered to the temporal bone, where otologic structures reside. [1][2][3]6 Damage to any part of the auditory mechanism can cause hearing loss, 7 and the reported incidence of RT-induced SNHL varies (from 0% to 54%) across studies.…”
Section: Introductionmentioning
confidence: 99%